2017
DOI: 10.3892/ol.2017.6173
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of −800G/A and +915G/C in TGF-β1 gene and lung cancer susceptibility

Abstract: We studied the relationship between the polymorphisms of −800G/A and +915G/C in transforming growth factor-β1 (TGF-β1) gene and lung cancer susceptibility. The sequence-specific primer polymerase chain reaction (PCR-SSP) technique was used to test 156 non-small cell lung cancer (NSCLC) patients that were selected as the observation group and 156 patients with pneumonia and tuberculosis that were selected as the control group (age and gender 1:1 proximal matching principle) and the polymorphisms of the first ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Grainger et al (1999) found that the rs1800469 SNP located in the promoter region is related to the expression level of TGF-b1. Di et al (2017) also found the SNP rs1800468 locus and the signal peptide rs1800471 locus also located in the promoter region are correlated with the expression level of TGF-b1 in plasma, and that specific alleles of these poly-morphisms were closely related to lung cancer susceptibility. Li et al (2019) also showed that the SNP located at the rs1800470 of the signal peptide of TGF-b1 gene is closely related to the occurrence of chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 85%
“…Grainger et al (1999) found that the rs1800469 SNP located in the promoter region is related to the expression level of TGF-b1. Di et al (2017) also found the SNP rs1800468 locus and the signal peptide rs1800471 locus also located in the promoter region are correlated with the expression level of TGF-b1 in plasma, and that specific alleles of these poly-morphisms were closely related to lung cancer susceptibility. Li et al (2019) also showed that the SNP located at the rs1800470 of the signal peptide of TGF-b1 gene is closely related to the occurrence of chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 85%
“…Finally, we obtained evidence of a correlation between adenocarcinoma in NSCLC and the single nucleotide polymorphism SNP. The results strongly imply that we have evaluated the association of two polymorphisms, including TGFβ1 (rs1800469) and (rs1800471), with pancreatic cancer risk in the Iranian population (47). Also, this study shows that high expression in the last stages of NS-CLC increases the concentration in the blood and the high mutation rate in TGFβ1 NSCLC patients.…”
Section: Discussionmentioning
confidence: 53%
“…TGFβ1 is a versatile cytokine that is vital for promoting local angiogenesis, extracellular matrix production, immunological evasion, cell heterogeneity adhesion, cell proliferation, invasion, metastasis, and other processes (8). Transforming growth factor β-induced protein is diffe-rentially expressed in transformed tissues.…”
Section: Introductionmentioning
confidence: 99%